Constraints and advances in high-solids enzymatic hydrolysis of lignocellulosic biomass: a critical review - da Silva, Ayla Sant’Ana; Espinheira, Roberta Pereira; Teixeira, Ricardo Sposina Sobral; de Souza, Marcella Fernandes; Ferreira-Leitão, Viridiana; Bon, Elba P. S. (Biotechnology for biofuels, 2020)
The industrial production of sugar syrups from lignocellulosic materials requires the conduction of the enzymatic hydrolysis step at high-solids loadings (i.e., with over 15% solids [w/w] in the reaction mixture). Such conditions result in sugar syrups with increased concentrations and in improvements in both capital and operational costs, making the process more economically feasible. However, this approach still poses several technical hindrances that impact the process efficiency, known as the “high-solids effect” (i.e., the decrease in glucan conversion yields as solids load increases). The purpose of this review was to present the findings on the main limitations and advances in high-solids enzymatic hydrolysis in an updated and comprehensive manner. The causes for the rheological limitations at the onset of the high-solids operation as well as those influencing the “high-solids effect” will be discussed. The subject of water constraint, which results in a highly viscous system and impairs mixing, and by extension, mass and heat transfer, will be analyzed under the perspective of the limitations imposed to the action of the cellulolytic enzymes. The “high-solids effect” will be further discussed vis-à-vis enzymes end-product inhibition and the inhibitory effect of compounds formed during the biomass pretreatment as well as the enzymes’ unproductive adsorption to lignin. This review also presents the scientific and technological advances being introduced to lessen high-solids hydrolysis hindrances, such as the development of more efficient enzyme formulations, biomass and enzyme feeding strategies, reactor and impeller designs as well as process strategies to alleviate the end-product inhibition. We surveyed the academic literature in the form of scientific papers as well as patents to showcase the efforts on technological development and industrial implementation of the use of lignocellulosic materials as renewable feedstocks. Using a critical approach, we expect that this review will aid in the identification of areas with higher demand for scientific and technological efforts.